2009
DOI: 10.1159/000239686
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Regulation under Hypnosis Assessed by Heart Rate Variability: Spectral Analysis and Fractal Complexity

Abstract: Objective: This study examined the effects of hypnosis on autonomic cardiac control. We hypothesized a modification of autonomic modulation of the heart rate with an enhanced vagal tone during hypnosis compared to baseline. Methods: In 12 healthy subjects (6 men and 6 women, 22.2 ± 1.0 years of age) ECG was recorded at baseline and during hypnosis. Heart rate variability parameters were obtained in the frequency domain (LFnu: low frequency normalized units, and HFnu: high frequency normalized units) and from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 106 publications
(90 reference statements)
3
30
1
1
Order By: Relevance
“…Furthermore, respiration and cardiac rhythm were not measured during fMRI data acquisition and therefore cannot be excluded as confounding factor in the data analysis. The influence of hypnosis on heart rate is still controversially discussed (Aubert et al, 2009;Emdin et al, 1996;Santarcangelo et al, 2008;VandeVusse et al, 2010). However, heart rate affects widely distributed areas of the brain (Birn et al, 2006;Shmueli et al, 2007) while effects observed here were rather circumscribed.…”
Section: Limitationsmentioning
confidence: 56%
“…Furthermore, respiration and cardiac rhythm were not measured during fMRI data acquisition and therefore cannot be excluded as confounding factor in the data analysis. The influence of hypnosis on heart rate is still controversially discussed (Aubert et al, 2009;Emdin et al, 1996;Santarcangelo et al, 2008;VandeVusse et al, 2010). However, heart rate affects widely distributed areas of the brain (Birn et al, 2006;Shmueli et al, 2007) while effects observed here were rather circumscribed.…”
Section: Limitationsmentioning
confidence: 56%
“…This finding, however, was not unequivocally supported (De Pascalis & Perrone, ; Gemignani et al, ; Hippel, Hole, & Kaschka, ; Ray et al, ). The conclusions of previous studies for the influence of hypnosis on the sympathetic nervous system (SNS) activity are similarly mixed with some studies showing decreased activity during hypnosis (Aubert et al, ; De Pascalis & Perrone, ; Debenedittis et al, ; Griffiths, Gillett, & Davies, ; Gruzelier, Brow, Perry, Rhonder, & Thomas, ; Gruzelier & Brow, ; Hippel et al, ) and studies that did not find decreased SNS activity (M. J. Diamond, ; Edmonston, ; Gruzelier, Allison, & Conway, ).…”
mentioning
confidence: 99%
“…A number of studies and a recent review argue that hypnosis enhances parasympathetic nervous system (PNS) activity (Aubert, Verheyden, Beckers, Tack, & Vandenberghe, ; Debenedittis, Cigada, Bianchi, Signorini, & Cerutti, ; S. G. Diamond, Davis, & Howe, ; van der Kruijs et al, ; VandeVusse, Hanson, Berner, & White Winters, ), which would indicate a relaxationlike effect (Sakakibara, Takeuchi, & Hayano, ). This finding, however, was not unequivocally supported (De Pascalis & Perrone, ; Gemignani et al, ; Hippel, Hole, & Kaschka, ; Ray et al, ).…”
mentioning
confidence: 99%
“…LF/HF rate was significantly lower in the hypnosis group compared to other two groups. In their study, Aubert et al [18] found that in healthy individuals LF levels were decreased in the hypnosis group while HF was increased and LF/HF rate was decreased. DeBenedittis et al [19] found similar results in healthy individuals undergoing hypnosis.…”
Section: Discussionmentioning
confidence: 92%